Guía de recursos didácticos digitales de la realidad histórica del cantón Pasaje orientado a la asignatura de estudios sociales del séptimo año de las escuelas fiscales de educación general básica. - Alcivar Galarza, Claudia Estefanía (2015)
This thesis project is located within the framework of two guiding lines: aspects of local historical content and use of digital educational resources on the social studies subject in the seventh year of B. G. E. It is an interdisciplinary proposal oriented public educational institutions in the basic educational level of the Pasaje city. The problem is derived from methodological aspects of teaching the history, like that the use of digital didactic resources does not exist or that incorporation is minimal in this subject. In addition, the development of topics on local historical content passes unnoticed as an object of study. As an alternative, it arises to structure didactic units that include like transverse axis the identity local supported from digital support, with base of theoretical content and multimedia that are inherent to the history of Pasaje city, this will help to claim the historic knowledge in different asset that can be tangible and intangible, and to generate impact as to opt for innovative methodological teaching proposals to provides a big comprehension and student participation. Procedures to finalize the project, is based on a methodology that descend from the general to particular aspects, with the diagnosis, objectivity, reliability and validity criteria, supported by methods required to achieve the correct development of a digital didactic resources guide about of local historical content.